Surface display of glycosylated Tyrosinase related protein-2 (TRP-2) tumour antigen on Lactococcus lactis - Kalyanasundram, Jeevanathan; Suet, Lin Chia; Ai, Adelene Lian Song; Abdul Rahim, Raha; A., Howard Young; Yusoff, Khatijah (BioMed Central, 2015)
Background:The exploitation of the surface display system of food and commensal lactic acid bacteria (LAB) for bacterial, viral, or protozoan antigen delivery has received strong interest recently. The Generally Regarded as Safe (GRAS) status of the Lactococcus lactis coupled with a non-recombinant strategy of in-trans surface display, provide a safe platform for therapeutic drug and vaccine development. However, production of therapeutic proteins fused with cell-wall anchoring motifs is predominantly limited to prokaryotic expression systems. This presents a major disadvantage in the surface display system particularly when glycosylation has been recently identified to significantly enhance epitope presentation. In this study, the glycosylated murine Tyrosinase related protein-2 (TRP-2) with the ability to anchor onto the L. lactis cell wall was produced in suspension adapted Chinese Hamster Ovary (CHO-S) cells by expressing TRP-2 fused with cell wall anchoring LysM motif (cA) at the C-terminus.